The Poetry o Culture. La esfera de Pascal, another motivo de Proteo - Cervera Salinas, Vicente (Anales de Literatura Hispanoamericana, 2010)
This essay revisits from an updated perspective the poetic function that culture had in Uruguayan writer José Enrique Rodó, specially in the hermeneutics of his summit creation, Motivos de Proteo (1909). The recreation and transculturation of the myths Rodó tackles is to be integrated in a highly honourable creating dimension where the transforming nature of Proteus gives rise to a system of thinking culture, of approaching its vitality, of conceiving writing, and of reinventing a poetic philosophy of flowing. Likewise, his work extrapolates the term “reason of Proteus” to one of Jorge Luis Borges’ paradigmatic essays, “La esfera de Pascal” (1951) by implementing the hypothesis that Borgesian idea of the essential and modulating metaphor that scaffold his essay, in the end, takes back to the “poetry of culture” which Rodó articulated in his Protean “reasons”.